Biology YouTube Videos with Focus Questions: Effects on Student Concept Understanding and Media-literacy Skills - Capati, Ariel Tacluyan (Jurnal Pendidikan MIPA, 2020)
This research determined the effects of Biology YouTube videos with focus questions on the concept understanding and media-literacy skills of students aged fifteen in the topic areas of Human Digestion, Heredity, Biodiversity and Interactions. A quasi-experimental research design using pretest-posttest was utilized. Students were divided into two randomly selected groups: experimental and control. Results revealed that Biology YouTube videos with focus questions (M = 10.68 ± 2.93) were as good as conventional teaching in enhancing student conceptual understanding (M = 10.69 ± 2.94) of Biology topics (p = .496). The study also showed that the strategy also developed media-literacy skills of the students (p = .000). Furthermore, it was found that conceptual understanding positively and significantly influenced media-literacy skills of students (r = .459; p = .003) and vice-versa (r = .459; p = .003). It is recommended that the strategy introduced in this study be used in facilitating media literacy in other allied science subjects, in other subjects, and in the teaching of media-literacy education to educators and students of different year levels. Keywords: biology youtube videos with focus questions, concept understanding, media-literacy skills. DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp01-11